53. Palmitoylethanolamide may have a role in enhancing pulmonary function and muscular strength in ALS patients. Issue 12 (December 2016) - Cambieri, C.; Ceccanti, M.; Onesti, E.; Tartaglia, G.; Frasca, V.; Rubino, A.; Inghilleri, M.
Abstract : Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease affecting motor neurons that leads to progressive paralysis of skeletal muscle. Studies of ALS have revealed defects in expression of acetylcholine receptors (AChRs) in skeletal muscle that occur even in the absence of motor neuron anomalies. The endocannabinoid palmitoylethanolamide (PEA) modified the clinical conditions in one ALS patient, improving muscle force and respiratory efficacy. Clinically, ALS patients treated with PEA showed a lower decrease in their forced vital capacity (FVC) over time as compared with untreated ALS patients, suggesting that PEA can enhance pulmonary function in ALS. In the present work, data were collected from a cohort of 76 ALS patients and 17 denervated patients. Our results strengthen the evidence for the role of skeletal muscle in ALS pathogenesis and pave the way for the development of new drugs to hamper the clinical effects of the disease.